2014
DOI: 10.1093/scan/nsu123
|View full text |Cite
|
Sign up to set email alerts
|

Is moral beauty different from facial beauty? Evidence from an fMRI study

Abstract: Is moral beauty different from facial beauty? Two functional magnetic resonance imaging experiments were performed to answer this question. Experiment 1 investigated the network of moral aesthetic judgments and facial aesthetic judgments. Participants performed aesthetic judgments and gender judgments on both faces and scenes containing moral acts. The conjunction analysis of the contrasts 'facial aesthetic judgment > facial gender judgment' and 'scene moral aesthetic judgment > scene gender judgment' identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(104 citation statements)
references
References 54 publications
5
97
1
Order By: Relevance
“…Moreover, the fact that the Golden Ratio plays a key role in human aesthetics and beauty [51,68] suggests that humans' taste for fairness and beauty are neutrally correlated. A recent f MRI (functional magnetic resonance imaging) study [69] lends support to our conjecture, by demonstrating that participants who performed evaluations of facial beauty (beautiful/common), and morality in scenes describing social situations (moral/neutral), exhibited common involvement of the orbitofrontal cortex (OFC), inferior temporal gyrus, and medial superior frontal gyrus.…”
Section: Summary and Concluding Remarkssupporting
confidence: 70%
“…Moreover, the fact that the Golden Ratio plays a key role in human aesthetics and beauty [51,68] suggests that humans' taste for fairness and beauty are neutrally correlated. A recent f MRI (functional magnetic resonance imaging) study [69] lends support to our conjecture, by demonstrating that participants who performed evaluations of facial beauty (beautiful/common), and morality in scenes describing social situations (moral/neutral), exhibited common involvement of the orbitofrontal cortex (OFC), inferior temporal gyrus, and medial superior frontal gyrus.…”
Section: Summary and Concluding Remarkssupporting
confidence: 70%
“…Most recently, an attempt by Wang and Mo [11] produced some exciting findings and should shed light on this issue. They compared the networks of moral beauty and facial beauty, and found that moral beauty representing advanced social needs recruited only the cortical reward region OFC, whereas facial beauty recruited both the OFC and the subcortical reward region putamen.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent fMRI study [11], our laboratory found that facial beauty involved both the subcortical reward region putamen and the cortical reward region OFC, while moral beauty involved only the OFC. The selective activation of the ventral striatum(VS) and OFC for different types of aesthetic was suggested to represent the association between aesthetics and the physiological or social demands.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of stimuli, for instance, researchers have used various types of media to present TPEs over the years, ranging from still images to brief sequences of still images to dynamic video clips . Furthermore, still images have included color photographs, grayscale photographs, and black‐and‐white schematic drawings . Video clips have comprised realistic depictions of social interactions, digital animations of human‐like avatars, and point‐light displays and stick‐figure displays of human movements .…”
Section: People Watching: Toward a Neuroscientific Perspectivementioning
confidence: 99%
“…Most importantly, there have been initial attempts to directly compare the effects of different impression‐formation tasks in the same study. In consequence, it has been shown that explicit social judgments, relative to basic perceptual tasks or TPE‐unrelated tasks, produce systematically enhanced activity in the PPN, AON, and MTN . Additionally, judgments about how an encounter unfolds (e.g., about which actions it entails) seem to result in stronger AON activation than judgments about why it unfolds (e.g., what types of motives or intentions people have).…”
Section: People Watching: Toward a Neuroscientific Perspectivementioning
confidence: 99%